Current issues in bilingualism : Cognitive and socio-linguistic perspectives - Schwartz, Mila; Tobin, Yishai; Leikin, Mark (Literacy Studies, Perspectives from Cognitive Neurosciences, Linguistics, Psychology and Education, 2012)
As populations become more mobile, so interest grows in bi- and multilingualism, particularly in the context of education. This volume focuses on the singular situation in Israel, whose complex multiculturalism has Hebrew and Arabic as official languages, English as an academic and political language, and tongues such as Russian and Amharic spoken by immigrants.   Presenting research on bi- and trilingualism in Israel from a multitude of perspectives, the book focuses on four aspects of multilingualism and literacy in Israel: Arabic-Hebrew bilingual education and Arabic literacy development; second-language Hebrew literacy among immigrant children; literacy in English as a second/third language; and adult bilingualism. Chapters dissect findings on immigrant youth education, language impairment in bilinguals, and neurocognitive features of bilingual language processing. Reflecting current trends, this volume integrates linguistics, sociology, education, cognitive science, and neuroscience.